2021
DOI: 10.1111/mpp.13124
|View full text |Cite
|
Sign up to set email alerts
|

PhcQ mainly contributes to the regulation of quorum sensing‐dependent genes, in which PhcR is partially involved, in Ralstonia pseudosolanacearum strain OE1‐1

Abstract: The gram‐negative plant‐pathogenic β‐proteobacterium Ralstonia pseudosolanacearum strain OE1‐1 produces methyl 3‐hydroxymyristate as a quorum sensing (QS) signal via the methyltransferase PhcB and senses the chemical through the sensor histidine kinase PhcS. This leads to functionalization of the LysR family transcriptional regulator PhcA, regulating QS‐dependent genes responsible for the QS‐dependent phenotypes including virulence. The phc operon consists of phcB, phcS, phcR, and phcQ, with the latter two enc… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
18
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
8
1

Relationship

2
7

Authors

Journals

citations
Cited by 17 publications
(19 citation statements)
references
References 50 publications
1
18
0
Order By: Relevance
“…Similar results were obtained with transcriptome analysis that PhcR is partially involved in the regulation of QS-dependent genes in R. solanacearum strain OE1-1, such as the genes norB , lecM , and xpsR were modulated by PhcR positively, and some flagellin biosynthesis-related genes and chemotaxis-related genes were negatively PhcR-dependent genes ( Takemura et al, 2021 ). In addition, the similar regulatory patterns were also found in modulation of the biosynthesis of ralfuranone, which is a SM and virulence factor produced by R. solanacearum ( Wackler et al, 2011 ), for the ralfuranone coding gene expression and biosynthesis is regulated positively by PhcA and negatively by PhcR ( Takemura et al, 2021 ). However, it is not yet clear whether PhcA and PhcR regulate the ralfuranone gene expression in a direct way similar to what we have found for the regulation of ralsolamycin.…”
Section: Discussionsupporting
confidence: 80%
“…Similar results were obtained with transcriptome analysis that PhcR is partially involved in the regulation of QS-dependent genes in R. solanacearum strain OE1-1, such as the genes norB , lecM , and xpsR were modulated by PhcR positively, and some flagellin biosynthesis-related genes and chemotaxis-related genes were negatively PhcR-dependent genes ( Takemura et al, 2021 ). In addition, the similar regulatory patterns were also found in modulation of the biosynthesis of ralfuranone, which is a SM and virulence factor produced by R. solanacearum ( Wackler et al, 2011 ), for the ralfuranone coding gene expression and biosynthesis is regulated positively by PhcA and negatively by PhcR ( Takemura et al, 2021 ). However, it is not yet clear whether PhcA and PhcR regulate the ralfuranone gene expression in a direct way similar to what we have found for the regulation of ralsolamycin.…”
Section: Discussionsupporting
confidence: 80%
“…The production of EPS I (a major extracellular polysaccharide of RSSC) and LecM (an RS-IIL lectin) is also dependent on the activation of the phc QS system (31, 32, 37). As shown in Pseudomonas aeruginosa (41), EPS and lectin may comprise the extracellular matrix of RSSC cells.…”
Section: Resultsmentioning
confidence: 99%
“…As expected, this bacterium harbors two chitinase genes (RSp0275 and RSp0924), three glucanase genes (cbh-A, egl, and RSc0818), and two lipase (or esterase) genes (RSp0138 and RSp0161) (29). The previous RNA-Seq comparison between OE1-1 and ∆phcB showed that the expression of these genes is under the control of the phc QS system (30)(31)(32). We thus constructed these gene-deletion mutants and evaluated their invasion ability into F. oxysporum chlamydospores.…”
Section: Extracellular Enzymes and Type Ii/iii Secretion Systems Are ...mentioning
confidence: 99%
“…We firstly compared the plasmid-based transformation frequencies of three methods, i.e., triparental mating, electroporation and natural transformation, in R. solanacearum . Triparental mating and electroporation are the two conventionally used methods for genetic transformation and gene deletion in RSSC ( Li et al, 2017 ; Corral et al, 2020 ; Takemura et al, 2021 ). Our results showed that natural transformation offered a significantly higher level of transformation frequency than the other two methods using plasmid DNA ( Figure 2A ).…”
Section: Discussionmentioning
confidence: 99%